Glioma pathogenesis‐related protein 1 induces prostate cancer cell death through Hsc70‐mediated suppression of AURKA and TPX2. Issue 3 (31st December 2012) - Li, Likun; Yang, Guang; Ren, Chengzhen; Tanimoto, Ryuta; Hirayama, Takahiro; Wang, Jianxiang; Hawke, David; Kim, Soo Mi; Lee, Ju-Seog; Goltsov, Alexei A.; Park, Sanghee; Ittmann, Michael M.; et al.
Abstract : In this study we report that expression of glioma pathogenesis‐related protein 1 (GLIPR1) regulated numerous apoptotic, cell cycle, and spindle/centrosome assembly‐related genes, including AURKA and TPX2, and induced apoptosis and/or mitotic catastrophe (MC) in prostate cancer (PCa) cells, including p53‐mutated/deleted, androgen‐insensitive metastatic PCa cells. Mechanistically, GLIPR1 interacts with heat shock cognate protein 70 (Hsc70); this interaction is associated with SP1 and c‐Myb destabilization and suppression of SP1‐ and c‐Myb‐mediated AURKA and TPX2 transcription. Inhibition of AURKA and TPX2 using siRNA mimicked enforced GLIPR1 expression in the induction of apoptosis and MC. Recombinant GLIPR1‐ΔTM protein inhibited AURKA and TPX2 expression, induced apoptosis and MC, and suppressed orthotopic xenograft tumor growth. Our results define a novel GLIPR1‐regulated signaling pathway that controls apoptosis and/or mitotic catastrophe in PCa cells and establishes the potential of this pathway for targeted therapies. Highlights: ► A 6900‐fold enhancement in the in‐vitro efficacy of targeted toxins. ► First report on usage of a purified saponin in‐vivo as enhancer of targeted toxin‐based tumor therapy. ► Reduced toxin dose with higher efficacy provides evidence for better translational research. ► Basis for testing in heterogenous tumor models and for numerous plant‐derived toxins.